Failure of botulinum toxin injection for neurogenic detrusor overactivity: Switch of toxin versus second injection of the same toxin. (22nd September 2015) - Peyronnet, Benoit; Castel‐Lacanal, Evelyne; Manunta, Andréa; Roumiguié, Mathieu; Marque, Philippe; Rischmann, Pascal; Gamé, Xavier
Abstract : Objectives: To evaluate the efficacy of a second injection of the same toxin versus switching to a different botulinum toxin A after failure of a first detrusor injection in patients with neurogenic detrusor overactivity. Methods: The charts of all patients who underwent detrusor injections of botulinum toxin A (either abobotulinumtoxinA or onabotulinumtoxinA) for the management of neurogenic detrusor overactivity at a single institution were retrospectively reviewed. Patients in whom a first detrusor injection had failed were included in the present study. They were managed by a second injection of the same toxin at the same dosage or by a new detrusor injection using a different botulinum toxin A. Success was defined as a resolution of urgency, urinary incontinence and detrusor overactivity in a patient self‐catheterizing seven times or less per 24 h. Results: A total of 58 patients were included for analysis. A toxin switch was carried out in 29 patients, whereas the other 29 patients received a reinjection of the same toxin at the same dose. The success rate was higher in patients who received a toxin switch (51.7% vs 24.1%, P = 0.03). Patients treated with a switch from abobotulinumtoxinA to onabotulinumtoxinA and those treated with a switch from onabotulinumtoxinA to abobotulinumtoxinA had similar success rates (52.9% vs 50%, P = 0.88). Conclusion: After failure of a first detrusor injection of botulinum toxin for neurogenic detrusor overactivity, a switch to a different toxin seems to be more effective than a second injection of the same toxin. The replacement of onabotulinumtoxin by abobotulinumtoxin or the reverse provides similar results.